The Study Of Nonverbal Means In The History Of Language - Berdimuratova Madina Khayrullayevna (Zien Journals, 2025)
In this article, the importance of national-cultural, gender, age-related, and social non-verbal codes in the study of non-verbal means, the role of these codes inlinguistic and cultural studies, and the classifications based on the different approaches of linguists to codes according to their meaning are highlighted.
Keywords: Linguististic culture; non-verbal codes; national-cultural code